Sleep disorders in cancer: interactions and intrinsic links - Chunxin Han; Nan Li; Xinlei Wang; Zhao Zhuang; Qianqian Cao; Shoushi Wang (Frontiers in Oncology)
The continuous improvement of early cancer screening and treatment technologies can significantly increase the survival time of cancer patients. Though cancer gradually becomes a chronic disease that can be controlled through continuous treatment, the scientific community has begun to pay attention to the physical and emotional issues that cancer and its treatment cause for cancer survivors. This review focuses on sleep disorders, which is quite common yet frequently overlooked in cancer survivors. Epidemiological and experimental data have demonstrated an inherent relationship between cancer and sleep disorders. This relationship may harm treatment adherence, quality of life, and survival rate of patients. This article systematically introduces the epidemiology, influencing factors, and underlying mechanisms of cancer-related sleep disorders. The impact of sleep disorders on cancer prognosis and current common treatment measures is also discussed to enhance the understanding of healthcare workers in addressing cancer complications.